Clinical uncertainty in primary care : the challenge of collaborative engagement - Launer, John; Sommers, Lucia Siegel (Springer New York, 2013)
This is a book about primary care clinicians and the clinical uncertainty endemic to their work. Even when seemingly straightforward, each patient raises unique questions regarding how best to listen to their complaints, empathize with their suffering, or respond to their silences.   This book is also about addressing uncertainty in primary care practice and engaging it. Engagement requires knowledge, explicit and tacit, placed in the service of a single patient's problem. It also requires carefully managed communication, facilitating dialogue with the patient and encouraging shared problem-solving.   Most importantly, this book is about collaborative engagement with case-based uncertainty in the setting of small groups of clinicians. Sommers and Launer contend that the medical profession's tradition of working independently should be augmented with an explicitly shared, collegial one of jointly creating wisdom through practice-based learning.   An international panel of expert clinicians and educators provides:  Perspectives on clinical uncertainty in the medical literature  A taxonomy of clinical uncertainty with patient examples  Analysis of the educator role to support clinicians in engaging uncertainty A compendium of small group methods for collaborative engagement with clinical scenarios  Analysis of the special challenges of collaborative engagement A mind-opening manifesto, Clinical Uncertainty in Primary Care will equip primary care clinicians, educators, public health and behavioral health professionals with resources for infusing practice with meaning through collegial collaboration. From the Foreword: "Lucia Sommers and John Launer, with the accompanying inputof their contributing authors, have done a deeply insightful and close to exhaustive job of defining clinical uncertainty. They identify its origins, components, and subtypes; demonstrate the ways in which and the extent to which it is intrinsic to medicine...and present a cogent case for its special relationship to primary care practice...Clinical Uncertainty in Primary Care not only presents a model of collegial collaboration and support, it also implicitly legitimates it." Renee Fox, Annenberg Professor Emerita of the Social Sciences, University of Pennsylvania